When Augmented Reality Met Art: Lessons Learned from Researcher–Artist Interdisciplinary Work - Cristina Portalés (Multimodal Technologies and Interaction, 2018)
Over the last few years, Augmented Reality (AR) technology has quickly evolved and today there is commercial software and hardware that allow the creation of AR experiences. However, it might still be cumbersome to create rich AR experiences without a deep knowledge of the technology. Artists have collaborated with IT experts during the last few years in order to enhance artistic pieces embedding AR technology, leading to the emergence of interesting collaborations between artists and engineers, computer scientists, architects, etc. The resulting works can be referred as AR Art. However, the interdisciplinary work behind these collaborations is usually not addressed. The aim of this paper is to review some of the reported AR Art work since the AR term was first coined in 1990, focusing on collaborations between different disciplines, especially during the early years, where art and technology became one. Additionally, the author reports her own experience in contributing to AR Art from an interdisciplinary perspective.